Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1186/1471-2202-13-57
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of musculocutaneous nerve reinnervation after vascular endothelial growth factor (VEGF) gene therapy

Abstract: BackgroundVascular endothelial growth factor (VEGF) is not only a potent angiogenic factor but it also promotes axonal outgrowth and proliferation of Schwann cells. The aim of the present study was to quantitatively assess reinnervation of musculocutaneous nerve (MCN) stumps using motor and primary sensory neurons after plasmid phVEGF transfection and end-to-end (ETE) or end-to-side (ETS) neurorrhaphy. The distal stump of rat transected MCN, was transfected with plasmid phVEGF, plasmid alone or treated with ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 39 publications
0
20
0
1
Order By: Relevance
“…for nerve transfers with synergistic function and axon count ratios are available in this animal model [30, 31]. Furthermore, using the ulnar nerve as donor and the long head of the biceps as recipient led to minimal motor or sensory deficit and thus minimal animal burden.…”
Section: Discussionmentioning
confidence: 99%
“…for nerve transfers with synergistic function and axon count ratios are available in this animal model [30, 31]. Furthermore, using the ulnar nerve as donor and the long head of the biceps as recipient led to minimal motor or sensory deficit and thus minimal animal burden.…”
Section: Discussionmentioning
confidence: 99%
“…41 In addition, VEGF is an effective protein that is able to promote axonal outgrowth and SC proliferation, and moreover, to stimulate SC infiltration and neovascularization after sciatic nerve transections. 42,43 In the present study, magnetic membranes via MFs were capable of increasing the expression and secretion of BDNF, GDNF, NT-3, and VEGF in SCs, which was further enhanced when SCs were seeded within scaffolds, and moreover, the gene expression and protein secretion of these neurotrophic factors through a time-course assay were reversible, which has shown that high prolonged expression of these factors is not necessarily positive in peripheral nerve repair. 44 All these findings indicated that magnetic nanocomposites via MFs are capable of regulating the expression and secretion of multiple NTs in a synergistic way in SCs.…”
mentioning
confidence: 52%
“…One advantage of ETSN over end-to-end neurotization is that with ETSN there is no need to sacrifice the surrounding nerves. One possible method of achieving better results in the future may be the use of neurotrophic factors to support reinnervation [8,17]. In cases of late obstetrical brachial plexus palsy, nerve surgery will likely be ineffective, and thus secondary surgery is called for to improve the hand, forearm, elbow and shoulder function and to prevent muscle contractures and bone shortening.…”
Section: Discussionmentioning
confidence: 99%